Electronic Stopping Powers for Protons in Polymers C5H8O2, C2H3CL and C2F4 (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The electronic stopping power of the proton reaction in the polymers C5H8O2, C2H3CL ,C2F4  for the energy ranging between (20-10000) MeV was studied. Numerical calculations and analysis of the results were carried out using the Matlab program for the Bohr and Beth equation and SRIM 2013 program.  All theoretical and practical values and results are presented in graphs. The stopping time of each polymer in protons was calculated.